PENGARUH EFIKASI DIRI TERHADAP PROKRASTINASI MELALUI SELF-REGULATED LEARNING - Dyan Kusumawati; siswandari siswandari; Nurhasan Hamidi (Universitas Sebelas Maret, 2020)
AbstractThis research are to investigate: (1) the direct influence of self efficacy on procrastination; (2) the direct influence of self efficacy on self-regulated learning; and (3) the indirect influence of self efficacy on procrastination through self-regulated learning. This research is ex-post facto research using quantitative approach. Samples of this research was 176 students who selected using proportionate stratified random sampling. Data of the research was collected through questionnaire. Data analyzed by using path analysis. The results of the research show that: (1) there was a significant direct influence of self efficacy on procrastination; (2) there was a significant direct influence of self efficacy on self-regulated learning; and (3) there were a significant indirect influence of self efficacy on procrastination through self-regulated learning. The result of this research are expected to reduce procrastination behavior by increasing self-efficacy and self-regulated learning. Keywords: Self Efficacy, Self-regulated Learning, Procrastination AbstrakPenelitian ini bertujuan untuk mengetahui: (1) pengaruh langsung efikasi diri terhadap prokrastinasi; (2) pengaruh langsung efikasi diri terhadap self-regulated learning; dan (3) pengaruh tidak langsung efikasi diri terhadap prokrastinasi melalui self-regulated learning. Jenis penelitian ini adalah penelitian ex-post facto dengan pendekatan kuantitatif. Sampel penelitian sebanyak 176 mahasiswa dipilih menggunakan teknik proportionate stratified random sampling. Teknik pengumpulan data menggunakan kuesioner. Analisis data menggunakan path analysis. Hasil penelitian menunjukkan bahwa: (1) terdapat pengaruh langsung yang signifikan efikasi diri terhadap prokrastinasi; (2) terdapat pengaruh langsung yang signifikan efikasi diri terhadap self-regulated learning; dan (3) terdapat pengaruh tidak langsung yang signifikan efikasi diri terhadap prokrastinasi melalui self-regulated learning. Hasil penelitian ini diharapkan dapat mengurangi perilaku prokrastinasi dengan meningkatkan efikasi diri dan self-regulated learning.Kata Kunci : Efikasi Diri, Self-regulated Learning, Prokrastinasi